PEREMPUAN PERSPEKTIF PEMIKIRAN HUKUM ISLAM MODERN - RIRIN FAUZIYAH; Burhanatut Dyana (Al Maqashidi : Jurnal Hukum Islam Nusantara, 2020)
Before Islam came, in many parts of the world women are subjected to humiliation andabuse. Women are considered as goods that can be traded, transferred, and inherited.Islam comes to improve the condition of women by elevating their status, giving themrights as men have rights over themselves and their assets, even women are no longerconsidered as inheritance assets, but as heirs who are also entitled to inherited property.Over time and the increasing education and knowledge possessed by women resulted inthe desire for women to get the same or equal rights as men. This condition seems tohave received support from many parties. This can be seen frome the emergence offemale warrior figures who passionately fight for women’s rights, such as: AminaWadud, Fatima Mernissi, Riffat Hasan, Rifa’ah Thahthawi, Qasim Amin and others.Among the few that are being discussed is: the creation of women, the concept ofnusyuz, distribution of inheritance, the existence of historical material control, lack ofwomen experts, very strong male hegemony, and against the developmentalismparadigm.